The ladder of agility-coordination. A tool to support the sprint acceleration phase in baseball (Original) (Revista científica Olimpia, 2021)
The implementation in physical conditioning routines of exercises which combine agility and coordination work looking for greater effectiveness in sprint acceleration capacity, is a pretty applicable way to maximize performance in baseball players. In view of the demand for this ability, the objective of this study is to use the agility-coordination ladder as a tool to favor the sprint acceleration phase in baseball. For that purpose, the defined experiment is planned in an experimental group in two moments: pre-test and post-test. The experimental stage takes place during the preseason, made up of a sample of thirty subjects with 26.12 years and an average weight of 77.47 kg. Moreover, an individualized training of short skipping is applied to the front, back and sides, free and overweight, ending with a sprint race in 10 meters, in addition to their usual training, five times a week and a competition match during the preseason that consisted of 8 microcycles. For the measurement of agility through the 5-10-5 the results obtained indicated significant improvements with a 5.25% Incrt and a reduction of the times of 0.24 s, with a speed interval 0.64 p / s of differences between pre-test and post-test, for a notable increase percent (% Incrt) of 4.80%. Overall, training on the agility-coordination ladder is shown to provide us with key information in the sprint acceleration phase.
Keywords: agility-coordination ladder; sprint speed; physical conditioning; test 5-10-5